2013
DOI: 10.1152/ajpheart.00434.2013
|View full text |Cite
|
Sign up to set email alerts
|

Focal myocardial infarction induces global remodeling of cardiac sympathetic innervation: neural remodeling in a spatial context

Abstract: Myocardial infarction (MI) induces neural and electrical remodeling at scar border zones. The impact of focal MI on global functional neural remodeling is not well understood. Sympathetic stimulation was performed in swine with anteroapical infarcts (MI; n ϭ 9) and control swine (n ϭ 9). A 56-electrode sock was placed over both ventricles to record electrograms at baseline and during left, right, and bilateral stellate ganglion stimulation. Activation recovery intervals (ARIs) were measured from electrograms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 30 publications
7
74
0
Order By: Relevance
“…Sympathetic nerve remodeling occurs in the ischemic area after MI injury [47,48]. MI increases cardiac GAP43 expression in the infarcted area [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic nerve remodeling occurs in the ischemic area after MI injury [47,48]. MI increases cardiac GAP43 expression in the infarcted area [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…These experiments were, however, limited by discordance of the ganglion stimulated and the region mapped, the decentralization of the LSG, and in some cases the complete removal of the RSG. Using electrophysiologic indexes to examine the functional innervation patterns of left and right sympathetic nerves on the heart, our group and others have demonstrated that the anterior wall of the heart is innervated predominantly by the RSG, while the posterior wall is innervated by the LSG (2,53,63). Cardiac sympathetic denervation is frequently performed for intractable arrhythmias, however, left cardiac sympathectomy is still widely performed.…”
Section: Discussionmentioning
confidence: 99%
“…LSGS and RSGS were performed with repeated square-wave pulses at a frequency of 4-Hz, 4-ms duration for 30 s. Stimulation amplitude was set at the amplitude at which blood pressure and/or heart rate increased by 10% (generally 1-8 mA). Cardiac sympathetic activation was also confirmed by surface T-wave changes and increases in heart rate and blood pressure as previously described (2). Bipolar electrodes were placed around each stellate ganglion (superior and inferior) for stimulation, with the cathode being superior.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings support the use of denervation via partial resection of the stellate ganglion to control arrhythmias (5,34,35) and to mitigate the progression of dilated CMY (36). Pathological changes within stellate ganglia that act to enhance neurotransmission create further electrical instability (37), increasing the risk of arrhythmias. Removal of a segment of the sympathetic chain may also eliminate these regions of the nervous system, which can potentially amplify sympathoexcitation.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%